Performance of ferrocement composites circular tanks as a new approach for RC tanks - Taha A. El-Sayed; Yousry B. Shaheen; Fatma H. Mohamed; Ragab M. Abdelnaby (Case Studies in Construction Materials, 2023)
Due to ferrocement high strength-to-weight ratio, flexibility, and adaptability to diverse forms and shapes, ferrocement had been seen as a possible alternative to traditional construction materials. In this research, the behavior of ferrocement composites tanks under static pressure loads was investigated experimentally and numerically. The investigational work includes testing twelve ferrocement composites circular tanks with dimensions 400 mm outer diameters, 500 mm height, and 25 mm thicknesses. The tanks are reinforced with welded and expanded steel meshes, as well as glass fiber mesh. According to the findings of the experiments, the ferrocement composites tanks have a higher failure load than traditional RC tanks, especially tanks reinforced with fiberglass polymer-mesh. The tank reinforced with three layers of Fiberglass polymers-mesh has the greatest first crack and ultimate load, as well as the highest ductility ratio and energy absorption. The non-corrosive fiberglass reinforcement mesh offers several advantages over structural steel meshes. In addition to its corrosion resistance, it boasts a significantly higher tensile strength (up to twice as high), is extremely lightweight, is non-conductive, and has very low thermal conductivity. The experimental results are compared to analytical models using (ANSYS ver. 16.2) software. The finite element simulations generated better results than the experimental data. The consistency ratio between the NLFEA and experimental results (Pu NLFEA/Pu exp.) was found to be outstanding, with an average of 0.902 and a standard deviation of 0.024. The correlation between the load-deflection curves of the NLFEA and experimental results was also found to be appropriate, with a mean correlation of 88 %. Furthermore, the matching ratio between the NLFEA and experimental results (∆u NLFEA/∆u exp.) was found to be high, with a mean matching ratio of 0.929 for all samples and a variation of 0.022. These results indicate that the NLFEA model accurately anticipates the performance of the investigated samples, making it a useful tool for predicting the behavior of similar structures. Ferrocement composite tanks have several advantages over traditional reinforced concrete (RC) tanks, including increased strength of up to 70 % when using ferrocement composites, resistance to cracking, cost-effectiveness, and resistance to corrosive substances. Finite element analysis (FEA) accurately predicts the behavior of ferrocement composite tanks, enabling engineers to design and optimize these tanks more efficiently. These advantages make ferrocement composite tanks a suitable option for various industrial and developing country applications, especially when cost and strength are crucial factors.